Effect of vegetal extracts on coccidiosis in fattening lambs fed with concentrate - Le Scouarnec J.; Benzoni G.; Guitard J.P.; Marzin D.; Guyonvarch A. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
Coccidiosis is an important pathology for sheep, causing important economic losses. Medicated so lutions are currently used but increase of coccidian resistance and demand for natural products from consumers is conducting to development of alternative solutions. A trial was conducted on four groups of 30 Lacaune lambs to assess the activity of a mix of plant extracts, commercially named Oilis, on the control of coccidiosis. It was compared to a negative control, to decoquinate (30 mg/kg of concentrate feed) and to another phytogenic product. Animals were followed from weaning (28 days of age) to slaughtering. All evaluated products were incorporated in the concentrate feed that was offered ad libitum, only completed by straw. Growth performances were evaluated by individual weighing every three weeks. Oocysts of coccidia were sampled in faeces and counted using Mac Master Cell at 28, 55, 76 and 97 days of age. Oilis improved growth on global period (p<0.05), particularly compared to decoquinate (+4.9%) and negative control (+8.3%). It enabled also the most important reduction of oocysts excretion at peak (-62.6%).This trial confirms the potency of some natural products as alternative to chemoprevention of coccidiosis in sheep.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)